(untitled) (Conferencea, 2022)
Kokand has been known by various names since the 10th century, but its heyday dates back to the 18th century, when the city became the capital of the Kokand Khanate. This city has preserved the ancient structure which consists of new and old parts. The new city was saturated in the 19th century. Commercial and enterprises, administrative buildings, banks, industrial palaces, the khan’s palace in the old part of the city – the Horde, monuments of folk architecture mosques, madrasas and monuments survived until the early 19th and early 20th centuries.